PENGETAHUAN IBU TENTANG PEMENUHAN GIZI SEIMBANG DENGAN PERILAKU PENCEGAHAN STUNTING PADA BALITA - Vara Dewi, Putri Anggun Diva (STIKES Widyagama Husada, 2025)
Stunting is a condition where a child's height is shorter than the age- standard due to chronic nutritional deficiencies. One of the government efforts through the Ministry of Health is to collaborate with community health centers and integrated healthcare having the 1000 Days of Life movement (HPK). To determine the correlation between mothers’ knowledge of balanced nutrition fulfillment and stunting prevention behavior in toddlers in Mulyorejo Village, Jember Regency. This study employed a quantitative design with a cross-sectional approach. The sample consisted of 148 mothers with toddlers aged 0-2 years. Sampling was conducted using simple random sampling techniques that was analyzed using Somers’D test. The study findings revealed a significant value of p=0.019 (<0.05) with a correlation coefficient of 0.182, indicating a significant correlation between mothers' knowledge of balanced nutrition fulfillment and stunting prevention behavior in toddlers. The majority of mothers had moderate knowledge with 105 demonstrating good stunting prevention behavior. There is a correlation between mother’s knowledge of balanced nutrition fullfilment and stunting prevention behavior in toddlers.